Clinicians' adherence to international guidelines in the clinical care of adults with inflammatory bowel disease. (4th May 2017) - Jackson, Belinda D.; Con, Danny; Liew, Danny; De Cruz, Peter
Abstract: Background: Although evidence-based guidelines have been developed for inflammatory bowel disease (IBD), the extent to which they are followed is unclear. The objective of this study was to review clinicians' adherence to international IBD guidelines. Methods: Retrospective data collection of patients attending a tertiary Australian hospital IBD clinic over a 12-month period. Management practices were audited and compared to ECCO (European Crohn's and Colitis Organization) guidelines. Results: Data from 288 patients were collected: 47% (136/288) male; mean age 43; 140/288 (49%) patients had ulcerative colitis (UC); 145/288 (50%) patients had Crohn's disease (CD); 3/288 (1%) patients had IBD-unclassified (IBD-U). Patient care was undertaken by gastroenterologists, trainees and general practitioners. Disease Management: Overall adherence to disease management guidelines occurred in 204/288 (71%) of patient encounters. Discrepancies between guidelines and management were found in: 25/80 (31%) of patients with UC in remission receiving oral 5-aminosalicyclates (5-ASAs) as maintenance therapy, and; 46/110 (42%) of patients with small bowel and/or ileo-cecal CD receiving 5-ASA. Preventive Care: Adherence to ≥1 additional component of preventive care was observed in 73/288 (25%) of patient encounters: 12/133 (9%) on thiopurines underwent annual skin checks; 61/288 (21%) of patients with IBD underwent a bone scan; 46/288 (16%) patients were reminded to have their influenza vaccine. Psychological care: Assessment of psychological wellbeing was undertaken in only 16/288 (6%) of patients. Conclusions: There remains a gap between adherence to international guidelines and clinical practice. Standardizing practice using evidence-based clinical pathways may be a strategy towards improving the quality of IBD outpatient management.